Developing Spiritual Education: Solutions to Realize People Winning in the Free Market Era (Journal Intellectual Sufism Research (JISR), 2020)
This research aims to find out ways and methods that can be done so that the spiritual development of education can be a solution to realize Indonesian society ready to compete in the free market era. This type of research is library research or library research that is designed through a qualitative approach using descriptive methods. Researchers as the main instrument in critically and in-depth study of relevant library materials. The results of the study pointed to k 's spiritual development can be used as a solution in creating a society ready to compete in a free market .